2018
DOI: 10.3892/ijmm.2018.3470
|View full text |Cite
|
Sign up to set email alerts
|

17β-estradiol protects INS-1 insulinoma cells from mitophagy via G protein-coupled estrogen receptors and the PI3K/Akt signaling pathway

Abstract: 17β-estradiol (17β-E2) is a steroid hormone that is known to exert effects on blood glucose homeostasis. The G protein‑coupled estrogen receptor (GPER) has been identified as a non-genomic estrogenic receptor, and is involved in numerous physiological processes, including cell survival, energy provision and metabolism. 17β-E2 may decrease apoptosis by binding to the GPER. The phosphoinositide 3-kinase (PI3K)/Akt signaling pathway is involved in physiological and pathological functions such as autophagy. The pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 47 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…It has been demonstrated that GPR30 activation can mediate PI3K/AKT pathway. 26 , 27 PI3K/Akt signaling pathway plays an important role in neuronal survival, proliferation and growth. Additionally, PI3K/Akt pathway can regulate microglial polarization and p-Akt contributes to microglia polarization to M2 type.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GPR30 activation can mediate PI3K/AKT pathway. 26 , 27 PI3K/Akt signaling pathway plays an important role in neuronal survival, proliferation and growth. Additionally, PI3K/Akt pathway can regulate microglial polarization and p-Akt contributes to microglia polarization to M2 type.…”
Section: Discussionmentioning
confidence: 99%
“…After cell density reached 80% once every 2 days, cells were passaged. After incubation in an FBS-free medium for 24 h at normal and high glucose with or without E2 and inhibitors, INS-1 cells were divided into the following groups (i) NG: normal glucose (5 mmol/L) for 24 h, (ii) NE: normal glucose + 0.1 μM E2 for 24 h, (iii) NGI: normal glucose + 15 μM G15 (Tocris Bioscience Minneapolis, USA) for 24 h, (iv) NAI: normal glucose + 1 μM Akt inhibitor (PF-04691502, Selleck Company, USA) for 24 h, (v) NMI: normal glucose + 10 μM mTOR inhibitor (rapamycin, Selleck Company, USA) for 48 h, (vi) HG: high glucose (30 mmol/L) for 24 h (17), (vii) HE: high glucose + 0.1 μM E2 for 24 h, (viii) HGI: high glucose + 15 μM G15 for 24 h, (ix) HAI: high glucose + 1 μM Akt inhibitor for 24 h, (x) HMI: high glucose + 10 μM mTOR inhibitor for 48 h (18).…”
Section: Methodsmentioning
confidence: 99%
“…It is worth noting that PI3K-Akt signaling pathway is one of the widely studied biological pathways. Phosphatidylinositol 3-kinases (PI3Ks) is a major downstream molecule of tyrosine kinases and G-protein coupled receptors, and it can activate Akt, glycogen synthase kinase-3 (GSK-3) through catalyzing the production of a second messenger 3,4,5-triphosphate phosphatidylinositol (PIP3), that transmit signals of various growth factors and cytokines into cells (Zhang L. et al, 2018). Thus, PI3K-Akt signaling pathway plays an important regulatory role in various biological processes such as cell proliferation, differentiation, apoptosis and glucose transport (Yu and Cui, 2016).…”
Section: Resultsmentioning
confidence: 99%